Targeting Caspase-1 in osteoarthritis: multi-omics insights into the effects of VX-765 on human chondrocyte function and phenotype - Mei, Jian; Schäfer, Nicole; Wei, Penghui; Kong, Zhiheng; Li, Shushan; Pann, Patrick; Ehrnsperger, Marianne; Johnstone, Brian; Matalova, Eva; Grässel, Susanne (Frontiers in Immunology, 2025)
BackgroundOsteoarthritis (OA) progression involves chronic inflammation, chondrocyte senescence, and extracellular matrix (ECM) degradation affecting all synovial joint tissues. To date, no regenerative OA drugs have been approved. Caspase-1, a core effector of the inflammasome, may contribute to OA via both canonical inflammatory and non-canonical functions, but its therapeutic value remains unclear.MethodsWe combined transcriptomic, proteomic, functional, and Mendelian randomization (MR) approaches. Using GSE168505 data, we analyzed CASP1, CARD gene family members (CARD16/17/18/8), and OA-related genes in OA- versus non-OA chondrocytes. We established an in vitro OA model by treating human chondrocytes with TNF-α ± VX-765 and assessed Caspase-1 activity, cell metabolism, and MMP secretion. We further conducted LC-MS/MS proteomic profiling, molecular docking, and MR analysis to identify molecular mechanisms and causal links.ResultsCASP1 and inflammatory/ECM-degrading genes (e.g., IL1B, MMP13) were upregulated in OA chondrocytes, whereas SOX9 was downregulated. CASP1 gene expression correlated positive with genes involved in senescence, inflammation, oxidative stress and ECM remodeling. Inhibitor VX-765 significantly inhibited Caspase-1 activity, reduced senescence, and enhanced migration in non-OA- and OA chondrocytes, with donor-dependent effects in OA chondrocytes. It also suppressed MMP13 secretion in OA chondrocytes. Integrated transcriptomic and proteomic analysis showed that VX-765 reprogrammed OA-activated signaling, significantly downregulating pathways related to senescence, inflammation, complement activation, and ECM organization, while upregulating interferon-α/γ responses. Moreover, in silico performed molecular docking analyses suggest that caspase-1 may directly bind MMP13, CTSD, ABL1, MRPS11, POLR21, SMAD2 and SOX9. MR analysis supported a causal link between increased CARD17/18/8 gene expression and reduced OA risk; several CASP1 SNPs (e.g., rs61751523) showed negative OA associations, suggesting a protective role.ConclusionsThis study demonstrates that Caspase-1 contributes to OA pathogenesis through both canonical and non-canonical mechanisms, and that VX-765 can alleviate chondrocyte dysfunction. The combined evidence supports VX-765 as a potential disease-modifying target for OA therapy. However, further investigation is warranted to clarify Caspase-1’s physiological roles, including possible off-target effects of its inhibitors, in cartilage and other joint tissues and the clinical relevance of inter-individual variability, with genomic variants (e.g., rs61751523) as one potential contributor, for therapeutic application.